PENGARUH PENGELOLAAN KEUANGAN PRIBADI TERHADAP PERILAKU PEMBAYARAN DIGITAL DAN KEPUTUSAN PEMBELIAN PRODUK ONLINE OLEH MAHASISWA JURUSAN PIPS UNIVERSITAS JAMBI - Erianita, Vina; Mayasari; Rifki, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of personal financial management based on the use of applications and manual methods on digital payment behavior and online product purchasing decisions of students in the PIPS Department at Universitas Jambi. The study used a quantitative approach with a survey method. The population of the study consisted of students from the 2022 cohort of the Economic Education, History Education, and Civic Education Study Programs. The research sample consisted of 167 respondents selected using the *purposive sampling* technique. Data collection was carried out through questionnaires, while data analysis used the MANOVA test with the assistance of SPSS version 22. The results showed that personal financial management had a significant influence on students’ digital payment behavior with a significance value of 0.000 < 0.05. In addition, personal financial management also had a significant influence on students’ online product purchasing decisions with a significance value of 0.000 < 0.05. The results of the multivariate test on Pillai’s Trace, Wilks’ Lambda, Hotelling’s Trace, and Roy’s Largest Root also showed a significance value of 0.000 < 0.05. Thus, simultaneously, personal financial management had a significant influence on digital payment behavior and online product purchasing decisions of students in the PIPS Department at Universitas Jambi.